To teach or not to teach?: being a newly qualified teacher in the post-compulsory sector during 2000-2004 - Matthews, Lynnette (2013)
This was a mixed-method study investigating factors which might affect newly-qualified teachers’ continued motivation to teach in the post-compulsory sector during the period 2000-2004. It aimed to identify the nature of demotivators and to measure the extent and impact of these on intentions to remain in teaching.